Scenarios for increased EU donor coordination: what is the right level of aid coordination? - Stephan Klingebiel; Pedro Morazán; Mario Negre (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
The need for more coordination in European development cooperation is acknowledged by most academics and practi-tioners. It emerges because there has been a strong increase in the level of fragmentation and proliferation of official development assistance (ODA) in recent years, despite the calls for stronger harmonisation and division of labour. Over the last 10 years, the European Union has invented a number of good technical solutions to overcome the disadvantages of fragmentation. However, the main challenges of inad¬equate Euro¬pean coordination are not related to technical coordi¬nation but to a clear policy commitment and guidance to improve further. Existing EU commitments on coordination in development cooperation and current mechanisms offer a mixed picture on the benefits and costs of EU coordination. The EU's efforts in the context of the international aid-effectiveness debate – and more specifically, aspects related to aid coordination – are not always accompanied by similar improvements at the national level of individual member states. Existing coordina¬tion efforts for the three main areas of coordination (policy, programming and implementation) have to be reviewed in order to adapt European development policy to the challenges. This includes a review of tools like division of labour, joint program¬ming, programme-based approaches and blending. Savings and other benefits from improved or increased coordination in EU development aid have to be assessed both qualitatively and quantitatively. Overall, there are three pivotal explanations for the current shortcomings with coordination at the EU level: 1. There is no consensus on what the right level of coordina¬tion is or should be. 2. The political economy of donor coordination is complex; there are strong incentives working against more coordination (such as the interest of member states in “visibility”). 3. The political economy of partner countries is complex as well and not always in favour of more coordination (fragmentation of donors as a strategy to diversify risks, e.g. in cases of enforced political conditionality). Savings in transaction costs seem to be the most evident and straightforward potential gains of coordination. Aid coordination at the EU level may create significant benefits both in terms of efficiency and in terms of impact. However, the calculation of transaction costs is challenging because the identification of the “inflection point”, where the bene¬fits surpass the costs, is virtually impossible and because qualitative benefits are difficult to assess. Currently, there are five model scenarios for shaping future EU development policy, of which only three would cor-respond to a progressive increase in EU coordination: i) “bilateralisation of EU aid policies”, ii) business as usual, iii) “different-speeds approach”, iv) “escalation of coordination” and v) “aid as an integrated policy”. For European development aid, a fully integrated approach would be, at least in theory, the best way to tackle fragmentation and the costs associated with it. However, member states do not really appear to be ready to fully “buy in” and “walk the talk”. An “escalation of coordination” (incremental increase of coordinated approaches) may imply a combination of short, medium and long-term coordination efforts in order to comply with international commitments through minor changes to the Lisbon Treaty.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Water